Women's place in `male space': gender and effect in Parliamentary contexts - Ross, Karen (2002)
This article is based on interviews conducted with 75 women Parliamentarians in the UK, Australia and South Africa between 1995 and 2000. It considers the differences that women can and do make both to the conduct of parliamentary politics but also to the policy agenda itself. The article suggests that there are differences in style and approach which are gender-dependent, but that policy differences based on gender are as likely to be rhetorical as real when voting behaviour and policy advocacy are carefully analysed. Other personal characteristics, such as political orientation and commitment to a more inclusive society, are as, if not more, significant indicators of policy support than gender alone. - Reproduced.
Keywords: Women in politics